STUDY OF FLOOD RUNOFF CHARACTERISTICS DUE TO LAND COVER CHANGE IN UPPER CILIWUNG RIVER BASIN USING HYDROLOGY MODEL GSSHA - TIGANA (12809009); Pembimbing : Dra. Atika Lubis, M.Si, PRINCENVO
Land cover changes in upper Ciliwung river basin gives a fairly dominant influence on the flood runoff at the downstream region, which is Jakarta. This phenomenon occurs in upper Ciliwung watershed due to Bogor, Puncak, and the surrounding area have undergone many changes in land cover, where this area has already changed into a tourist area. This study aimed to determine the relationship of land cover change on river discharge, related to flooding incidents in 2005 and 2007.To see this relationship, then performed a simulationof river discharge at the outlet point on Katulampa by using hydrologic distribution model GSSHA (Gridded Surface Subsurface Hydrologic Analysis). Using a measuremen rainfall data from Gadog, Gunung Mas, Cilember, and Katulampa station aswell as land cover data from MODIS satellite images, the results fromthe simulation will be calibrated through a two-stage calibration to obtain the results of a simulation that approximates the discharge observations. First with the value of the surface roughness and the second with the value of effective rainfall.The results shows that land cover change in study area during 2005 and 2007 has increased the peak discharge. It is shown that the peak discharge in flood event of 2005 will increased 1,02 times when the same event is simulated with the 2007 land cover. In conjunction, the peak discharge of 2007 flood event will decrease to 0,81 times when the same event is simulated with 2005 land cover.